2012
DOI: 10.1590/s0034-71672012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento do adolescente sobre vacina no ambiente da Estratégia Saúde da Família

Abstract: The study aimed to identify the knowledge of adolescents, residents in an area where the Family Health Strategy is present, about the vaccination calendar and acquired protection. The nature of this inquiry was quantitative, sectional and it was developed through home inquiry, from 2008 March to April. The data had been typed and processed by using the Epi-Info software. It was noted that the adolescents in this study were unaware of the recommended vaccines present in the Ministry of Health calendar. Consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 13 publications
1
9
0
12
Order By: Relevance
“…Corroborating the findings of the present study regarding knowledge of vaccines, previous studies reported that 48.6% of participants cited the yellow fever vaccine and only one-third were aware of both the hepatitis B and tetanus vaccines 16,17 . A study conducted in the State of Pará showed that only 26.87% of participants were aware of the existence of a vaccine against hepatitis B 15 , while a study carried out in Teresina found that hepatitis B was the third best-known vaccine after the rubella and yellow fever vaccines 16 . Greater knowledge about the rubella and yellow fever vaccines may be due to national campaigns against these diseases with widespread media coverage.…”
Section: Vaccine Education Region Total Central Northeast Northwest Ssupporting
confidence: 87%
See 1 more Smart Citation
“…Corroborating the findings of the present study regarding knowledge of vaccines, previous studies reported that 48.6% of participants cited the yellow fever vaccine and only one-third were aware of both the hepatitis B and tetanus vaccines 16,17 . A study conducted in the State of Pará showed that only 26.87% of participants were aware of the existence of a vaccine against hepatitis B 15 , while a study carried out in Teresina found that hepatitis B was the third best-known vaccine after the rubella and yellow fever vaccines 16 . Greater knowledge about the rubella and yellow fever vaccines may be due to national campaigns against these diseases with widespread media coverage.…”
Section: Vaccine Education Region Total Central Northeast Northwest Ssupporting
confidence: 87%
“…Although almost 100% of the adolescents thought that vaccination was important, the large majority lacked knowledge about the vaccination schedule, mentioning, for example, being vaccinated against diseases or infections that are not vaccination-preventable, such as HIV-AIDS, syphilis, candidiasis, gonorrhea, and herpes simplex, and vaccination against dengue fever, which is still not available on the public health system. A study conducted in the State of Piauí, found that 60.2% participants reported that they were unaware of the adolescent vaccine schedule 16 .…”
Section: Vaccine Education Region Total Central Northeast Northwest Smentioning
confidence: 99%
“…A busca na base de dados da BVS apresentou como resultado inicial 35.002 artigos, apenas no descritor não vacinação. Verificou-se na busca: texto completo (16.925), assunto principal conhecimentos, atitudes e pra tica em sau de (804), idioma espanhol, portugue s e ingle s (791), intervalo u ltimos 10 anos (779), paí s de afiliaça o Brasil (11).…”
Section: Resultsunclassified
“…Os motivos alegados pelas crianças e pais, nos trabalhos, para na o vacinar crianças e adolescentes foram: temor a agulha e a dor 11 ; necessidade de maiores informaço es sobre a vacina e estudo. Motivos para na o vacinar um filho adolescente foi que a decisa o caberia ao filho, somente se houvesse indicaça o me dica 12 ; receio dos efeitos colaterais, esquecimento, falta de tempo devido a vida ocupada e falta de conhecimento sobre vacinas -na o havendo diferença significativa nestas razo es entre escolas pu blicas e privadas 13 ; medo de experimentar dor durante a aplicaça o, receio de desaprovaça o familiar, incerteza sobre a efica cia da vacina e segurança, e medo de possí veis efeitos colaterais 14 .…”
Section: Discussionunclassified
“…A adolescência pode ser considerada um período de mudança que influencia de forma significativa os aspectos físicos, sexuais, cognitivos e emocionais 7 É possível compreender a adolescência como um período do desenvolvimento situado entre a infância e a fase adulta, delimitado pela OMS como a faixa etária dos 10 aos 19 anos de idade 8 . É uma fase de reorganização emocional, em que os conflitos resultantes de alterações biológicas, psíquicas e sociais são comumente exacerbados através do comportamento 7 .…”
Section: Introductionunclassified